Comparisons of Ocular Anatomic Differences of Lens-Subluxated Eye with or without Acute Angle Closure: A Retrospective Study - Hong-Liang Lin; Yong-Jie Qin; Yu-Lin Zhang; Yu-Qiao Zhang; Yong-Yi Niu; Yan-Lei Chen; Yun-Yan Hu; Wen-Juan Xie; Hong-Yang Zhang (Journal of Ophthalmology)
Purpose. To compare ocular anatomy differences of lens subluxation between eyes with or without acute angle closure (AAC). Methods. This is a retrospective and case-control study. Sixty cases with mild lens subluxation were recruited. Among them, 30 eyes with acute angle closure were assigned to the AAC group and 30 eyes without AAC were assigned to the non-AAC group. The anterior segment was quantitatively evaluated by ultrasound biomicroscopy (UBM). The axial length (AL) was measured with IOL Master. All patients underwent lens extraction surgery and were followed up for six months. Results. The history of blunt trauma accounted for 22 (73.3%) cases in the AAC group and 21 (70%) cases in the non-AAC group. Fifteen (50%) patients in the AAC group had iridotomy history, and high intraocular pressure recurred. The UBM analysis showed that the average central chamber depth of the affected eyes in the AAC group was 1.82 mm, which was significantly shallower than that in the fellow eyes (2.58 mm, P<0.05) or both eyes in the non-AAC group.Both eyes in the AAC group presented a shorter AL and shallower anterior chamber than the eyes in the non-AAC group. Conclusions. An asymmetrical anterior chamber between bilateral eyes is an important feature in lens subluxation-induced AAC. The crowded anterior chamber and shorter AL might be the anatomic basis for the eye with lens subluxation-induced AAC.